KEBIJAKAN SANKSI PIDANA PENJARA TERHADAP PENYALAHGUNAAN NARKOBA BAGI DIRI SENDIRI - Sumartini Dewi (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2016)
Evil is not reduced but is increasing, this is not exactly user policy and laws, if the law itself becomes a factor kriminogen and viktimogen. Imprisonment sanction policies relating to drug abuse for yourself stipulated in Article 127 paragraph (1) letter a, b, c of Law 35 of 2009 and against the abuse of psychotropic substances for selfregulated in Article 60 paragraph (5) of the Constitution of Number 5 of 1997, using the drug for themselves to have the intent that drug use is done without a doctor's supervision. Drug abusers for themselves viewed as criminals and victims, therefore, in formulating sanctions to be applied against drug abusers for themselves should be pursued through rational policy. In the prevention of drug abuse for yourself, where criminal sanctions are still needed, although it focuses on the repressive nature of which is after the crime occurred. However, criminal sanctions is an effort to substitute the latter when other efforts have been inadequate.